The Effect of Layout, Prices and Food Delivery Services on Purchase Decisions at Culinary BUMDES in Wunut Village: Pengaruh Tata Letak, Harga dan Layanan Food Delivery Terhadap Keputusan Pembelian Pada BUMDES Kuliner di Desa Wunut - Islamiyati, Dian; F, Amelya Khusnul (Procedia of Social Sciences and Humanities, 2022)
This study aims to analyze the influence of layout, price dan food delivery service on purchasing decisions in the bumdes culinary place in wunut village. This Research uses a descriptive qualitative research method with a literature review approach that involves collecting information through various sources relating to library data collection methods or research extracted through various library information. In addition, researchers also made observations through quesionnaires distributed online and filled in via Google Form by the research subjects, potencil buyers. The resulf of the study show that layout, price and food delivery service influence purchasing decision on the bumdes culinary place in wunut village. The main aspect highlighted in this article is how there three variables can influence purchasing decisions and increase the number of visitors. Next, the discussion will be classified into several sub-discussions. First, will analyze the efficiency of the layout of the culinary bumdes. Second, the effect of price and food delivery service on purchasing decision at the culinary bumdes in wunut village.